The bacterial flora of the udder of goats - TZORA, A.; SKOUFOS, J.; TSINAS, A.; FOTOU, K.; KARAMOUTSIOS, A.; KALYVA, Z.; NIKOLAOU, K.; FTHENAKIS, G. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Aims of the study were to identify microbial flora in healthy caprine udders and to evaluate possible sources of principal caprine mastitis pathogens. Samples of teat duct material and mammary secretion from goats in two farms (flock A, polyparous n=30; flock B, polyparous n=60) were collected from both glands, four times during the lactation period. Subsequently, bacteriological investigation took place from 200 udders of slaughtered goats (n=100). Mammary gland skin swabs were examined bacteriologically from one farm (flock C, polyparous n=60) four times, one before and three during the lactation period. In all milk samples, cytological examinations were negative. Conventional bacteriological techniques were used. Bacterial contamination was found in 93% of samples from the skin of the teat, in 44% of teat duct scraping samples, in 6% of teat duct material samples and in 4% of mammary secretion samples. Different bacterial species were isolated, mainly coagulase negative staphylococci. This investigation showed smaller proportion of contamination in the teat canal than in the outer surface of the teat skin, indicating that teat provides innate defensive systems against bacterial invasions.